Decrease dimensions and weight of gas turbine regenerators by internal flow swirling - Шевцов, Анатолий Павлович; Кузнецов, Валерий Валерьевич; Мовчан, Сергей Николаевич; Ким, Светлана Георгиевна (Eastern-European Journal of Enterprise Technologies, 2013)
The analysis of the efficiency of axial vane, screw and tangential internal swirling flow to intensify the flow of heat transfer processes in regenerators to reduce their dimensions and weight are presented. Calculated variation of the Nusselt number and the pressure drop as a function of the angle of swirling, diameter and wall thickness of pipe. Determined for the best way to reduce weight and size, and calculated parameters depending on the different sizes of heat transfer surface pipe of the regenerator. The analysis of results shows that at the identical values of hydraulic losses the most value of the determined index is arrived at the use of тенгенциального swirler as compared to an axial-shoulder-blade and screw.